(untitled) (Revista de Ensino em Artes, Moda e Design, 2024)
This dossie presents the collection of texts selected for the 16th edition of the journal and highlights the importance of linking sustainability and social innovation to training processes and paths in higher education, especially in the areas of Arts, Fashion and Design.